1986
DOI: 10.1046/j.1537-2995.1986.26687043613.x
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged storage of red cells at 4° C

Abstract: One of the events associated with red cell storage at 4 degrees C is the development of an increasing proportion of echinocytes. Vesicles also may bud off the spicules, presumably leading to a decreased surface-to-volume ratio and decreased deformability. Pursuing the hypothesis that increasing the surface tension of the cells by increasing their volume might reduce the tendency toward echinocytosis and extend refrigerated storage time, packed red cells were resuspended in a solution hypotonic (210 mOsm) with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0
5

Year Published

1990
1990
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(34 citation statements)
references
References 7 publications
2
27
0
5
Order By: Relevance
“…In a previous publication [6] we described a red-cell resuspension solution that substantially extended the main tenance of ATP and yielded 24-hour in vivo survival ex ceeding 75% for as long as 14 weeks. The solution was hypotonic for solutes that do not penetrate the red cell and contained ammonium chloride in addition to sodium or potassium phosphate, glucose, mannitol and adenine at a pH of 7.1.…”
mentioning
confidence: 99%
“…In a previous publication [6] we described a red-cell resuspension solution that substantially extended the main tenance of ATP and yielded 24-hour in vivo survival ex ceeding 75% for as long as 14 weeks. The solution was hypotonic for solutes that do not penetrate the red cell and contained ammonium chloride in addition to sodium or potassium phosphate, glucose, mannitol and adenine at a pH of 7.1.…”
mentioning
confidence: 99%
“…Another factor acting in the same direction is the swelling of the cells in the hypotonic medium. Meryman et al [24] have suggested that the increase in surface tension could suppress the shedding of vesicles. A secondary effect of the decreased loss of cell membrane is the better mainte nance of cholesterol and phospholipids (unpublished data).…”
Section: Resultsmentioning
confidence: 99%
“…Literature data showed that antioxidants given either to blood donors [47] or to storage solutions [2,48] improve RBCs storage parameters by reducing free radical cell damage. The most promising results could be expected when antioxidants effectively inhibit cation leakage [49,50].…”
Section: Discussionmentioning
confidence: 99%
“…Beside the problems connected with sterility of the blood samples (the absence of pathogenic infection and viruses) there is a general problem of cell survival during the storage and after the transfusion. Cryopreservation of RBCs in highly concentrated glycerol media results in about 80% survival of de-frozen cells [1,2]. However, the method complexities (expensive materials used and post-storage cryoprotectant removal problems) limit the use of cryopreserved blood.…”
Section: Introductionmentioning
confidence: 99%